Caffeine exposure causes downregulation of the expression of genes related to osteogenesis and chondrogenesis in Zebrafish (Danio rerio) - Bertassoli, Bruno Machado; Santana, Gilcinea de Cassia; Nogueira, Julia Meireles; Paula, Rayan Silva de; Jorge, Erika Cristina; Guilherme, Helder de Oliveira; Alves, Endrigo Gabellini Leonel; Reis, Amanda Maria Sena; Serakides, Rogéria; Ocarino, Natália Melo (Brazilian Journal of Veterinary Pathology, 2024)
With the aim of evaluating the effects of caffeine on the expression of gene transcripts related to osteogenesis and chondrogenesis, during zebrafish embryonic development the embryos were divided into five groups: control (without caffeine), 0.25 mM caffeine, 0.5 mM caffeine, 1.0mM caffeine, and 2.0mM caffeine. Embryos were placed in cell culture plates with aquarium water at 280C for 72 hours post-fertilization (hpf). Embryonic development was followed at times of six, 12 hpf, 24 hpf, 30 hpf, 48 hpf, 54 hpf, and 72 hpf. At 72 hpf, the expression of Sox9a, runx2b, osteocalcin, osteopontin, collagen 2a1, and bmp2a was analyzed using real-time RT-PCR. The 0.25mM caffeine group showed embryonic development that was visually similar to the control group despite having a significantly lower relative expression of bmp2a, runx2b, and collagen 2a1. In the 0.5mM and 1mM caffeine groups, morphological alterations such as tail folding, pericardial edema, and yolk sac deformation were observed, and the relative expression levels of bmp2a, runx2b, and collagen 2a1 were significantly lower. In contrast, osteocalcin expression was significantly higher than in the control group. In the 2mM caffeine group, the embryos did not hatch until 72 hpf and showed tail docking and pericardial and yolk sac edema. The relative expression of bmp2a and runx2b was significantly lower, whereas that of osteocalcin, osteopontin, and collagen 2a1 did not differ from that of the control group. We conclude that caffeine altered the expression of gene transcripts related to osteogenesis and chondrogenesis in zebrafish embryos, even in embryos without visible morphological changes.